A meta-analysis of the prognostic value of the TyG index in heart failure - Cai, Yuqin; Yang, Meijie; Ma, Shuting; Zhang, Jinyun; Huang, Bin; Yu, Baili (Frontiers in Endocrinology, 2025)
BackgroundHeart failure (HF) is a serious cardiovascular disorder with a poor prognosis, which affects the quality of life and survival in patients. The triglyceride-glucose (TyG) index, a new biomarker for insulin resistance (IR) in the body, has attracted widespread attention from researchers investigating cardiovascular disease (CVD). This study was aimed at assessing the prognostic value of the TyG index in HF patients by a meta-analysis, thereby providing clinicians with a new predictive tool.MethodsPubMed, Cochrane, EMBASE, and Web of Science were searched for studies (from inception to March 2025) on the association of the TyG index with the prognosis of HF. Meta-analysis was conducted using Stata15. Such association was assessed using a random effects model in conjunction with the hazard ratio (HR) and its 95% confidence interval (CI). In addition, subgroup analysis, publication bias analysis, and sensitivity analysis were performed.ResultsNineteen studies were included with 44275 HF patients. A significant association was found between an increase in the TyG index and an increase in the risk of all-cause death (ACD) in HF patients (HR=1.70, 95% CI: 1.40-2.08, P<0.001). Increased TyG index predicted major adverse cardiovascular events (MACEs) (HR=2.37, 95% CI: 1.80-3.13, P<0.001) and cardiovascular death (CV death) (HR=1.63, 95% CI: 1.01-2.61, P<0.001). Subgroup analysis showed an association of increased TyG index with a poor prognosis regardless of ejection fraction, and the presence or absence of diabetes. Dose-response analysis showed no linear dose-response relationship (DRR) of the index with ACD, MACEs or CV death.ConclusionThe TyG index is closely associated with the prognosis of HF. Therefore, it can be used as a prognostic tool for the assessment of HF. A high TyG index may indicate a high risk of ACD and CV events. Therefore, monitoring of the TyG index is significant for risk assessment and management of HF patients. Future studies on the use of the TyG index in therapeutic decision-making for HF are needed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024562063.